Influenza Neuraminidase Characteristics and Potential as a Vaccine Target - Creytens, Sarah; Pascha, Mirte N.; Ballegeer, Marlies; Saelens, Xavier; de Haan, Cornelis A. M. (Frontiers in Immunology, 2021)
Neuraminidase of influenza A and B viruses plays a critical role in the virus life cycle and is an important target of the host immune system. Here, we highlight the current understanding of influenza neuraminidase structure, function, antigenicity, immunogenicity, and immune protective potential. Neuraminidase inhibiting antibodies have been recognized as correlates of protection against disease caused by natural or experimental influenza A virus infection in humans. In the past years, we have witnessed an increasing interest in the use of influenza neuraminidase to improve the protective potential of currently used influenza vaccines. A number of well-characterized influenza neuraminidase-specific monoclonal antibodies have been described recently, most of which can protect in experimental challenge models by inhibiting the neuraminidase activity or by Fc receptor-dependent mechanisms. The relative instability of the neuraminidase poses a challenge for protein-based antigen design. We critically review the different solutions that have been proposed to solve this problem, ranging from the inclusion of stabilizing heterologous tetramerizing zippers to the introduction of inter-protomer stabilizing mutations. Computationally engineered neuraminidase antigens have been generated that offer broad, within subtype protection in animal challenge models. We also provide an overview of modern vaccine technology platforms that are compatible with the induction of robust neuraminidase-specific immune responses. In the near future, we will likely see the implementation of influenza vaccines that confront the influenza virus with a double punch: targeting both the hemagglutinin and the neuraminidase.